Utilizing Technology to Improve the Quality of Learning in Indonesia: Challenges and Consequences for Arabic Teachers - Mahyudin Ritonga; Sobhan Sobhan; Bambang Bambang (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
Islamic boarding schools are identical to traditional learning because they ignore and do not respond to technological developments. This study aims to describe the media used in Islamic boarding schools in teaching Arabic, teachers' perceptions of technology-based media, and opportunities to change the media used in Arabic learning in Islamic boarding schools. This study was conducted with a qualitative approach in Islamic boarding schools where students were selected according to their needs. Data were collected by observation, interviews, and documentation studies. Based on the results, the Batang Kabung Islamic Boarding School used traditional learning media. However, there are open opportunities to apply technology-based media because of the openness of pesantren in accepting changes with an internet connection, human resources for education staff, and students' ability to operate technology-based learning media. The consequences faced by Islamic boarding schools are curriculum revisions, more operational costs, adjustment of methods with learning media, and the need to improve teacher competencies in utilizing technology-based media.